Research On Photovoltaic Mppt Control Method Based On Improved Bas Algorithm And Variable Step-Size Inc Method - Li, Wenli (2024)
Solar energy has received widespread attention and has been developed due to its distinct advantages, such as abundant reserves and not restricted by geography. However, the PV module is easily affected by external environments in practical applications, leading to a decrease in PV power. MPPT technology for the PV power system is an effective method to improve the efficacy of PV electricity conversion. Commonly used control methods include CVT method, perturbation and observation method, and incremental conductance method. These methods differ greatly in terms of required parameters, algorithm complexity, tracking speed, tracking accuracy, hardware requirements, etc. In this study, a MPPT control method based on IBAS and VSINC was proposed to obtain a better performance in MPPT.